2000
DOI: 10.1053/seiz.2000.0425
|View full text |Cite
|
Sign up to set email alerts
|

Is intranasal midazolam an effective rescue medication in adolescents and adults with severe epilepsy?

Abstract: The aim of this study was to determine whether intranasal midazolam is a safe and effective rescue medication in adolescent and adult patients with severe epilepsy. This field trial was designed to test the feasibility of the use of intranasal midazolam as an alternative to rectal diazepam in a cohort of patients with severe epilepsy who require rescue medication as part of their treatment. A dose of intranasal midazolam (5 mg if the patient weighed less than 50 kg and 10 mg if the patient weighed over 50 kilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 20 publications
2
44
0
1
Order By: Relevance
“…Familiarity with the IN administration of midazolam may now be increasing among carers because of its use as a rescue medication for prolonged epileptic seizures. 9 It is also in line with current guidelines on minimal physical intervention, 10 as clinical holding of the patient is only required for the briefest of moments to administer the aerosol spray. Indeed, with the use of a tissue wiping the nose to distract the patient immediately before the spray is administered, little or no holding may be required.…”
Section: Sneezedsupporting
confidence: 62%
“…Familiarity with the IN administration of midazolam may now be increasing among carers because of its use as a rescue medication for prolonged epileptic seizures. 9 It is also in line with current guidelines on minimal physical intervention, 10 as clinical holding of the patient is only required for the briefest of moments to administer the aerosol spray. Indeed, with the use of a tissue wiping the nose to distract the patient immediately before the spray is administered, little or no holding may be required.…”
Section: Sneezedsupporting
confidence: 62%
“…Interestingly, t 1/2 values obtained in rats were much closer to our data than those obtained in humans, 55.4 min and 105.5 min for MDZ and DZP, respectively [27]. In light of the pharmacokinetic data obtained in our study, it can be concluded that: a) there is a species difference between rabbits (and rodents) and humans with regard to the elimination rate of benzodiazepines, but there is no apparent difference in the absorption process, resulting in a very short onset of time in both MDZ and DZP administrations; b) the longer time to reach peak plasma level (t max ) of DZP relative to MDZ may explain the clinical advantage in the use of midazolam over diazepam in the treatment of acute seizures [11]. The microemulsion system of this study provided a high drug concentration of 25 mg/g and (or even 50 mg/g) compared with the 5 mg/ml MDZ-HCl and DZP in plain solutions.…”
Section: Resultsmentioning
confidence: 99%
“…It is also socially embarrassing, and although difficult to administer during con-vulsions can be used only in children and in a few cases in adolescents; 3) it is highly lipophilic and therefore has a large volume of distribution. Repeated doses are sometime needed and its accumulation may lead to complications such as bradypnea and even respiratory arrest [10,11]. Diazepam is also available in tablets; however, the oral route is not accessible during seizures and cannot be used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In smaller children the titration of doses as per weight is a problem. A significant amount of the fluid can be swallowed and absorbed from the gastrointestinal tract, which decreases the bioavailability and therefore reduces efficacy [10]. Furthermore, treatment failure may occur due to poor technique in delivering an adequate volume of midazolam liquid.…”
Section: Discussionmentioning
confidence: 99%